1998
DOI: 10.1046/j.1365-2109.1998.00256.x
|View full text |Cite
|
Sign up to set email alerts
|

Polyculture of silver barb, Puntius gonionotus (Bleeker), Nile tilapia, Oreochromis niloticus (L.), and common carp, Cyprinus carpio L., in Vietnamese ricefields: fish production parameters

Abstract: The fish production parameters of five polyculture combinations, consisting of small and large silver barb, Puntius gonionotus (Bleeker), small and large Nile tilapia, Oreochromis niloticus (L.), and small common carp, Cyprinus carpio L., fingerlings in three replicates, were investigated in a rice‐fish culture experiment (duration 149 days) conducted in the Mekong Delta, Vietnam. The survival rate was not significantly (P > 0.05) affected by the polyculture combination, but when grouped according to species, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 9 publications
1
16
0
1
Order By: Relevance
“…From these first observations, it seems that O. niloticus is not exceptionally well suited for culture in rice fields. Also other authors (Haroon 1998; Rothuis et al . 1998c) noted that tilapia spp.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…From these first observations, it seems that O. niloticus is not exceptionally well suited for culture in rice fields. Also other authors (Haroon 1998; Rothuis et al . 1998c) noted that tilapia spp.…”
Section: Discussionmentioning
confidence: 78%
“…Rothuis et al . (1998c) suggested that there could be a synergistic growth effect between B. gonionotus and O. niloticus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esta ampla faixa de variação, característica da região sul do país, que apresenta estações bem definidas, não afetou a sobrevivência das espécies cultivadas neste experimento. Para ROTHUIS et al (1998), o desenvolvimento do arroz e o baixo nível da água tem um impacto no ambiente aquático, assim como no peixe. Freqüentemente a fertilização realizada cedo no ciclo da cultura do arroz e a baixa densidade de plantas neste estágio, estimula o desenvolvimento de fitoplâncton, principal responsável pelos altos níveis de oxigênio na água.…”
Section: Resultsunclassified
“…Furthermore, survival in NA‐50 was although significantly lower than NA‐25, the fingerling recovery in terms of number was greater in the former which also yielded a significantly higher biomass (both gross and net yield/tank) than the latter. The fingerling size in NA‐50 (3.03 ± 0.14 g) was also large enough for stocking (Rothuis et al 1998). Thus, the study indicated that under non‐aerated condition, rearing the fry to fingerling at 50/m 2 (NA‐50) is advantageous over those at 25 and 75/m 2 .…”
Section: Discussionmentioning
confidence: 99%